The Influence of Co-Worker, Work Conflict, and Work Environment on Employee Perfomance (Case Study at PT Petindo Era Tangguh) - Mei Lie; Pujiarti Pujiarti (eCo-Buss, 2024)
The element of human resources is a crucial element in the success of a company. However, the aspect of human resources is often overlooked and its functions and roles within an organization are underestimated. Its presence is even considered a burden in the company because it only incurs expenses. By having good human resources, performance can be improved. The issues occurring at PT Petindo Era Tangguh include co-workers who are undisciplined, have poor ethics, exhibit individualism, lack cooperation, have low loyalty, and are unable to solve problems. Additionally, employees feel that the work environment is perceived as unsafe and uncomfortable, causing them to feel threatened and resulting in a decline in performance of employee. The goal of this research is to understand certain significant workplace conflicts, rekans, and kerja environments in relation to employee work at PT Petindo Era Tangguh in a parsial manner. Colleagues, work environment, and work conflict  are the independent variables of this study, meanwhile employee performance is the dependent variable. The method used is a quantitative deskriptif approach that uses a kuesioner, observation, and wawancara. The outcomes of this study indicate that coworkers, work conflicts, and working conditions affect employee performance.